Galician Public Funding for Translated Works (2008-2016) - Montero Küpper, Silvia (Madrygal. Revista de Estudios Gallegos, 2017)
Literary translation is a social action and as such is comprised of several parts which include its reception as a product of the cultural industry, the publishing houses, translation policies, translators, etc. Decisions relating to the purpose of the translations (whether political, commercial or cultural) arise from the political, cultural and aesthetic positions that prevail at the time. Traditionally, most publications in the Galician language are published by private Galician publishing houses. Those published by public institutions amount to about 10% of all Galician published works while the ones published by national publishing houses account for 25% of the same. This paper analyses the calls for public grants announced for translation of published texts in Galicia from the beginning of the current economic crisis (2008) to recent times (2016). These calls have caused an impact on the promotion and planning of translations within private publishing houses. Economic factors and the award criteria used during the past years are analysed, in the light of a translation policy for a subaltern cultural system.
Keywords: Translation Funding; Politics of Literary Translation; Translation and Subaltern Cultures; Galician Cultural System.